PERAN PROFITABILITAS DALAM MEMODERASI INVESTASI, LEVERAGE DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Prayitno, Andi; Naz'aina, Naz'aina; Biby, Sapna (Universitas Malikussaleh, 2020)
ABSTRACT This study aimed to examin the effect of investment, leverage and dividend policy on firm value with profitability as a moderator in Non-Financial Services Companies in Indonesia during the 2014-2018 period. The number of samples in this study were 20 Non-Financial Services Companies that Paid dividend regularly during 2014-2018. The type of data was secondary data in the form of panel data obtained from the company's Annual Report. Data analysis method was Panel Data Regression. The results of this study found that leverage and profitability had a positive effect on firm value, where investment and dividend policy did not effect significantly on firm value, and profitability was able to moderate the effect of leverage on firm value, but was unable to moderate the effect of investment and dividend policy on firm value Keywords: investment, leverage, dividend policy, profitability and firm value